Hot air pretreatment alleviates browning of fresh-cut pitaya fruit by regulating phenylpropanoid pathway and ascorbate-glutathione cycle - Li, Zilong; Li, Bingru; Li, Meiqi; Fu, Xiaodong; Zhao, Xiuming; Min, Dedong; Li, Fujun; Li, Xiaoan; Zhang, Xinhua (Postharvest biology and technology, 2022)
The effects of hot air (HA) pretreatment on quality, phenolic accumulation and antioxidant activity of fresh-cut pitaya fruit were investigated. It was found that 42 °C HA pretreatment for 3 h effectively alleviated the browning of fresh-cut pitaya fruit stored at both 4 °C for 14 d and 20 °C for 48 h. To better understand the physiological mechanisms of HA on browning alleviation, higher storage temperature at 20 °C was used to accelerate and amplify the wounding responses. The results demonstrated that HA pretreatment delayed the wound induced biosynthesis of phenolic compounds of fresh-cut pitaya fruit during earlier storage period but enhanced their contents and maintained higher antioxidant activity during the later stage of storage. It retarded but enhanced the activation of key enzymes (PAL, 4CL and C4H) and their relative gene expressions involved in the phenylpropanoid pathway. Moreover, HA pretreatment suppressed the activities of enzymes associated with oxidative browning of phenolics (PPO and POD), activated ascorbate-glutathione (AsA-GSH) cycle and inhibited the wound induced proliferation of ROS production which could cause oxidative damage of fresh-cut pitaya fruit. These findings suggested that pretreatment with HA could be an efficient and feasible approach for the browning alleviation and quality retention of fresh-cut pitaya fruit, and the phenylpropanoid metabolism and AsA-GSH cycle played crucial roles in this process. •Hot air (HA) pretreatment alleviated browning of fresh-cut pitaya fruit.•HA pretreatment delayed but enhanced the wound-induced phenolic accumulation.•HA pretreatment reduced PPO and POD activities.•HA pretreatment enhanced antioxidant system and reduced ROS level.